Reliability improvement of railway vehicles: a review - Arfiansyah, Oky; Handoko, Yunendar Aryo (Jurnal Nasional Aplikasi Mekatronika, Otomasi dan Robot Industri (AMORI), 2024)
Railway vehicles are mobile parts of the operating basis on railways that are used for the movement on the track. Reliability is an important factor in the operation of railway vehicles as they play an important role in ensuring the safety and efficiency of railway operations. The complexity of subsystem structures can affect vehicle reliability, and failure or damage to components can lead to operational disruption or system failure. Reliability improvement techniques focus on minimizing failures, reducing unplanned downtime, and ensuring efficient and safe operation of railway vehicles. These techniques include maintenance strategies, design optimization, spare parts management, training, skilled management, and reliability analysis. This paper aims to discuss these reliability improvement techniques globally and specifically examine the performance of railway vehicles in Indonesia. Prioritizing reliability improvement is applied to minimize unexpected breakdowns and failures, thereby improving passenger experience, punctuality, and safety. By reducing disruptions, reliability improvements contribute to smooth train travel, minimizing delays, and creating a safer environment. In addition, improved reliability in railway transportation systems increases efficiency, benefiting passenger satisfaction, economic growth and development. Safe, reliable, and efficient transportation facilitates the movement of goods and people, encourages trade and enhances regional connectivity, ultimately supporting sustainable economic development.